EVALUATION OF THE VARIETY AND LINES OF TWO-SEASONAL SOFT WHEAT FOR HEAT RESISTANCE (British Journal of Global Ecology and Sustainable Development, 2024)
This article analyzes the heat resistance of protein coagulation indicators of the leaves of the variety and the wheat yarn line at the beginning of the spiking phase. The KR19-19thDSBWYT-29782 line with the highest performance was chosen for the purpose of creating a grade for an unfavorable external environment.